Synthesis and characterization of hydroxyapatite biocomposite using Syzygium aromaticum for biomedical application - Kavya Menon; Anusuya Nagaraj; Anjali Sudha; Neveen Kumar Kalagatur; Seethalakshmi Subramaniam; Suja Samiappan (Next Nanotechnology)
The study aimed to prepare a hydroxyapatite biocomposite with clove (Syzygium aromaticum) bud ethanol extract and demonstrate antibacterial and antioxidant functions. The phytochemical profile of clove bud ethanol extract showed prominent presence of eugenol and gallocatechin by LC-MS/MS analysis. Hydroxyapatite and a biocomposite of hydroxyapatite with clove bud ethanolic extract were prepared using sol-gel and precipitation methods, respectively. Fourier Transform Infrared analysis showed that clove bud ethanolic extract biomolecules were successfully imparted onto the hydroxyapatite surface. The X-ray diffraction study revealed that as-synthesized hydroxyapatite and biocomposite of hydroxyapatite with clove bud ethanolic extract were crystalline and had crystal sizes of 42 nm and 126 nm, respectively. The field emission scanning electron microscopy showed that hydroxyapatite and the biocomposite of hydroxyapatite with clove bud ethanolic extract were spherical in shape and agglomerated. The average particle size distribution of hydroxyapatite and biocomposite of hydroxyapatite with clove bud ethanolic extract was 298.39 and 478.48 nm, respectively. Energy-dispersive X-ray analysis revealed that hydroxyapatite consists of calcium, phosphorus, and oxygen. In contrast, the biocomposite of hydroxyapatite with clove bud ethanolic extract contain carbon in addition to calcium, phosphorus, and oxygen. Thermogravimetric analysis revealed that hydroxyapatite and biocomposite of hydroxyapatite with clove bud ethanolic extract were thermostable. The biocomposite of hydroxyapatite with clove bud ethanolic extract exhibited potential antibacterial action, and the zone of inhibition against S. aureus, E. faecalis, S. enterica, and E. coli was determined as 20.10 ± 0.08, 25.08 ± 0.07, 14.20 ± 0.04, and 24.08 ± 0.08 mm, respectively. Biocomposite of hydroxyapatite with clove bud ethanolic extract exhibited potential antioxidant activity. Hydroxyapatite and biocomposite of hydroxyapatite with clove bud ethanolic extract showed hemolysis < 2 % and were found hemocompatible and safe. Thus, the as-synthesized biocomposite of hydroxyapatite with clove bud ethanolic extract could help overcome oxidative stress-mediated complications and microbial infections in orthopaedics.